Health education and health development in the 21st century. - Wattanaburanon, A.; Piyaaramwong, P. (Chulalongkorn Medical Journal, 2023)
It is stated that health education takes a very important role for developing community health. Since health education is the process of educating people and community, they will be able to get health knowledge, good health attitude and practice by themselves for the better health. However, even though the progress of technology, medical and public health in the 21st century, people are still confronted with health problems, especially the problems from preventable diseases. In this era, we have to consider the outcomes of community health learning and its support system. As for the community health learning outcomes, we should focus on health literacy, environmental literacy, life and career skills, learning and innovation skills, and also information, media and technology skills related to health. As for the support system, there are 4 aspects of concentrations which are standards and assessment in health education, community health education methods, professional development in health and environmental management for health learning.